2018
DOI: 10.1136/bmjopen-2017-018563
|View full text |Cite
|
Sign up to set email alerts
|

Compassionate care intervention for hospital nursing teams caring for older people: a pilot cluster randomised controlled trial

Abstract: ObjectiveCompassionate care continues to be a focus for national and international attention, but the existing evidence base lacks the experimental methodology necessary to guide the selection of effective interventions for practice. This study aimed to evaluate the Creating Learning Environments for Compassionate Care (CLECC) intervention in improving compassionate care.SettingWard nursing teams (clusters) in two English National Health Service hospitals randomised to intervention (n=4) or control (n=2). Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 27 publications
(32 reference statements)
0
20
0
Order By: Relevance
“…It is essential, therefore, that research instruments are developed that do not exclude this population. Observation-based measures such as QuIS hold promise here because they do not require care recipients to have the abilities to, for instance, complete a written questionnaire and they largely remove the psychological threat of rating one's own care ( Bridges et al., 2018 ; Goldberg and Harwood, 2013 ; Gould et al., 2018 ). Our recruitment strategy in this study aimed to optimise the inclusion of people with cognitive impairment, although the number recruited with cognitive impairment was low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is essential, therefore, that research instruments are developed that do not exclude this population. Observation-based measures such as QuIS hold promise here because they do not require care recipients to have the abilities to, for instance, complete a written questionnaire and they largely remove the psychological threat of rating one's own care ( Bridges et al., 2018 ; Goldberg and Harwood, 2013 ; Gould et al., 2018 ). Our recruitment strategy in this study aimed to optimise the inclusion of people with cognitive impairment, although the number recruited with cognitive impairment was low.…”
Section: Discussionmentioning
confidence: 99%
“…(1993) reported that increases in the QuIS-rated quality of interactions following a change of service location were accompanied by improvements in residents’ cognitive impairments, mood and functional capacity, providing some evidence of QuIS’ validity in relation to quality of life. Subsequent studies established the responsiveness of QuIS to changes in service quality in a range of healthcare settings ( Bridges et al., 2018 ; Brooker, 1995 ; Fritsch et al., 2009 ; Gould et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Expressing compassion in a caring relationship could enhance a feeling of being trusted by another person (LoCurto & Berg, ) and compassionate training could help nurses to express their compassion towards older persons more explicitly (Adam & Taylor, ; Dewar et al, ). Although this type of training is usually for student nurses (Adam & Taylor, ), it could help more experienced nurses as it would enable them to reflect on their own behaviour (Gould et al, ). Nurses who have had this training might also be better able to assess and discuss the informal carer's attitude and behaviour towards the person.…”
Section: Discussionmentioning
confidence: 99%
“…Although this type of training is usually for student nurses (Adam & Taylor, 2014), it could help more experienced nurses as it would enable them to reflect on their own behaviour (Gould et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Reproduced fromGould et al 2018 120. © Article author(s) (or their employer(s) unless otherwise stated in the text of the article) 2018.…”
mentioning
confidence: 99%